(untitled) - Bes, D. R. (Singapore, 1990)
This book introduction about the classical treament of systems described by means of collective coordinates. The Hilbert spaces associated with collective coỏdinatos, the BRST treatment...
Keywords: Invariance principles (Physics),Vấn đề tổng thể,Many-body problem; Nguyên lý bất biến (vật lý)